PENEGAKAN HUKUM LINGKUNGAN DALAM BIDANG PENGELOLAAN SAMPAH SEBAGAI PERWUJUDAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE DI KOTA SURAKARTA - Verdy Verdianto; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
Waste management is still a problem which is not yet solved. This research aims to study the problems in waste management in Surakarta. It was a doctrinal/normative legal research using the statute approach, which then analyzed qualitatively. There are laws related to waste management in Indonesia, they are Law number 18 Year 2008 on Waste Management, Law No. 32 of 2009 on the Protection and Environmental Management, and some more. The law enforcement in waste management refers to the legal system i.e. structure, substance, and culture. There are two kinds of waste management law enforcement; preventive and repressive. The effectiveness of the enforcement refers to the combination of structure, substance, and law cultures of the community. The effective law enforcement on waste management also indicates the commitment of the government, both local and national, in applying the principles of Good Environmental Government in order to build community awareness on a good and healthy environment